2020
DOI: 10.1039/c9sm01916b
|View full text |Cite
|
Sign up to set email alerts
|

The role of the medium in the effective-sphere interpretation of holographic particle characterization data

Abstract: Holographic particle characterization measurements can be interpreted with the effective-sphere model to obtain the size, refractive index and porosity of porous and irregularly shaped colloidal particles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 31 publications
4
40
0
Order By: Relevance
“… 2 , 3 , 24 , 25 Their measured refractive indexes are intermediate between that of the particle’s matrix and that of the medium. 15 , 16 HVM has been demonstrated to yield accurate characterization data for such inhomogeneous and aspherical particles 2 , 16 , 24 26 through the effective medium theory of light scattering. 15 , 27 In this case, the population of particles near the medium refractive index is naturally identified with protein aggregates, as distinct from emulsion droplets.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… 2 , 3 , 24 , 25 Their measured refractive indexes are intermediate between that of the particle’s matrix and that of the medium. 15 , 16 HVM has been demonstrated to yield accurate characterization data for such inhomogeneous and aspherical particles 2 , 16 , 24 26 through the effective medium theory of light scattering. 15 , 27 In this case, the population of particles near the medium refractive index is naturally identified with protein aggregates, as distinct from emulsion droplets.…”
Section: Resultsmentioning
confidence: 99%
“…Changes in the properties of the medium due to added excipients can influence the results of HVM measurements, most notably for porous particles whose pores are perfused with the medium. 15 , 16 The effective refractive index reported by HVM for such particles is intermediate between the refractive index of the medium and the refractive index of the porous particles’ matrix material. This mechanism was invoked in the discussion of protein aggregates’ properties presented in Figure 2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This technology has similarly been used to distinguish bacteria from plastic beads and oil in water 43 since each of those species is composed of materials of different refractive indexes. A study of porous silica particles showed that THC is able to detect subtle changes in particle composition 44,45 . The ability to detect small changes in particle composition is due to the effective sphere model and the effective medium theory 44,46 .…”
Section: Holographic Approach To Yeast Viabilitymentioning
confidence: 99%